Balancescapes: an investigation into the effectiveness of site-scale water harvesting in St. Louis, Missouri - Haid, Wesley Adam (Kansas State University, 2014)
Outdoor landscape irrigation is a prodigious consumer of potable water and accounts for more than 50% of urban water use in the United States. It is therefore imperative to reserve potable water for essential uses. The variability of recent drought trends coupled with the prediction of more intense, less frequent storms and rising water costs suggest the need to recycle as much free water as possible to meet non-essential irrigation demands. But is it possible to harvest enough water on-site to meet landscape water requirements with little to no reliance on municipal water? If not, how can design professionals adjust planting plans to bring the landscape water demand into equilibrium with potential supply while still meeting aesthetic objectives? This report uses predictive performance-based modeling to answer these questions. The author chose three study sites in St. Louis, Missouri to determine if the water demand of the existing landscapes can be supplied by collecting enough rainfall runoff and air conditioning condensate. Site selection depended on site size, differing harshness of localized environmental conditions, and ability to collect and generate large quantities of runoff and condensate water. Methods included a literature review, site inventory/analyses, estimation of plant water requirements using evapotranspiration data, estimation of rainfall runoff from various surfaces, and estimation of air conditioning condensate using thermodynamic equations. Findings show that landscape water needs for two of the three sites can be potentially met by on-site water sources with little to no reliance on municipal water. This was due to limited landscape areas compared to larger paved areas, the building footprint, and large quantities of air conditioning condensate produced during the hottest months. Under existing conditions, the third site was out of water balance. Consequently, the author undertook a planting re-design to convert low priority turf expanses to a naturalistic meadow requiring less water. Additionally, the author performed a return on investment analysis for both retrofit conditions and new construction. Overall, this research demonstrates that site-scale water harvesting for landscape irrigation purposes is a viable option to curtail reliance on municipal water supplies in the Midwest and similar climates.
Keywords: Water harvesting; Landscape architecture; Sustainability; Air conditioning condensation; Landscape Architecture (0390)